Finite Element Analysis of Electromagnetic Forming Process Applied on Thin Wall Metallic Workpieces - Sorin Pasca (Journal of Electrical and Electronics Engineering, 2009)
The paper deals with numerical simulationsof magnetoforming process applied on thin wallmetallic workpieces. Finite element models aredeveloped using ANSYS Multiphysics as a support.The transient electromagnetic field phenomena aresequentially coupled with mechanical/structuralphenomena. The electromagnetic part of modelassumes the magnetic field – electrical circuit couplingand in the structural part, the deformed workpiece areconsidered as viscoplastic material with rate dependentmaterial properties.